AL-I'JÄ€Z AL-á¹¢AUTÄª FÄª AL-QURÄ€N AL-KARÄªM WA NAMÄ€ZIJUH AL-MUâ€˜Ä€á¹¢IRAH: DIRÄ€SAH TÄ€RÄªKHIYYAH TAá¸¤LÄªLIYYAH - Ismu Ridha; Abu Zinah, Manshur Mahmud; Subhi, Muhibbul; Syam, Futry (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2024)
Al-Qur'an is the most miracle of the Prophet Muhammad who has a various forms of miracles (wujÅ«h al-i'jÄz), one of them is the â€œAudio Miracleâ€ or al-I'jÄz al-á¹¢autÄ«. Therefore, this research aims to present and analyze the discourse of i'jÄz al-SautÄ« in the Qur'an. To achieve this, researchers use a historical approach by studying the history of the revelation of the Qur'an and its transmission to humanity, then this research uses an analytical approach to several examples of verses containing i'jÄz al-SautÄ« in a contemporary perspective, and finally, the research uses an istinbÄá¹i approach, namely formulating a study in conclusion form. This research obtained several findings, First, I'jÄz al-SautÄ« is the most visible form of i'jÄz of the Qur'an, because it can be felt by all readers and listeners, not only limited to Arabs, but for all humans. Second, i'jÄz al-SautÄ« is an important form of i'jÄz which was initially conveyed from Allah to Jibril as. and then to the propet Rasulullah using the oral voice method (musyÄfahah). Third, among the secrets of the i'jÄz al-SautÄ« is the beautiful and detailed arrangement between the harmony of the sounds that provide comfort and tranquility for the soul and the harmony of the meaning contained therein. Fourth, Umar bin Khattab's islamic event is the most obvious proof of the influence of the sound of the sentences of the Qur'an on the soul of the listener.